Transanal Endoscopic-Assisted Pull-Through Colectomy for Children with High Intestinal Aganglionosis - Ulrike Metzger; Armin-Johannes Michel; Mircia-Aurel Ardelean; Roman Patrick Metzger (MDPI AG, 2022)
Intestinal aganglionosis in children is a common cause of neonatal and infantile obstruction or ileus. Diagnosis is based on a histologically proven absence of enteric ganglion cells in deep biopsies of the gut wall. Therapeutic goal is a one-stage repair with a resection of the affected segment. The endorectal pull-through (ERP) can be performed entirely transanally in a lot of the cases. In patients with difficult preparation or a high aganglionosis ERP often needs to be assisted by laparoscopy or laparotomy. We present two cases with a technical modification performing a totally transanal pull-through colectomy without any trocars other than an umbilical camera trocar. The procedure starts with a classical endorectal technique. Usually, the transanal preparation is limited by reaching the colon descendens. A camera trocar is inserted and under laparoscopic vision the preparation is completed placing the instruments directly via the opened anus. After reaching the healthy colon segment, the pull-through is completed transanally. One of the main advantages of ERP is the sparing dissection. Our modification combines advantages of laparoscopy and ERP. The umbilical camera allows an excellent view while the instruments for dissection are used like with ERP without any further trocar or traction of the anal sphincter. The dispensation of any transanal trocar allows a higher grade of freedom in preparation and possibly a smaller trauma on the distal anal channel.